Cognitive Aspects of Adults and Older Adults with Hearing Loss, Users or not of Hearing Aids: A Meta-Analysis (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: adults; older adults; hearing loss; hearing aids; cognition; cognitive decline